Assessing the Impact of Climate Change on Urban Cultural Heritage - Aktas, Yasemin D. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a printed edition of the Special Issue titled "Assessing the Impact of Climate Change on Urban Cultural Heritage" hosted at the Atmosphere journal. This topic has been chosen in light of cities' ever-growing role and immense potential in the climate adaptation and mitigation discourse and the particular challenges regarding urban heritage making and conservation. It is critical to recognise the complex set of factors governing the physical, social and political future of urban heritage in cityscapes in constant transformation and in an era of planetary urbanisation. The 10 papers (seven research papers, two reviews and one opinion piece) that comprise the issue give a broad cross-section of the issues pertinent to this important topic - accounts on practices and conceptual/methodological improvements in energy retrofit and reuse, risk mapping, urban planning, climate vulnerability assessment, and community engagement by 38 authors from seven countries are used to delineate the implications of current and likely future climates on heritage materials and systems, knowledge and practice gaps, as well as steps that need to be taken to ensure both their safeguarding and their valorisation to achieve climate resiliency.